1999
DOI: 10.1016/s0307-904x(99)00007-4
|View full text |Cite
|
Sign up to set email alerts
|

Current grid-generation strategies and future requirements in hypersonic vehicle design, analysis and testing

Abstract: Recent advances in computational power enable computational fluid dynamic modeling of increasingly complex configurations. A review of grid generation methodologies implemented in support of the computational work performed for the X-38 and X-33 are presented. In strategizing topological constructs and blocking structures factors considered are the geometric configuration, optimal grid size, numerical algorithms, accuracy requirements, physics of the problem at hand, computational expense, and the available co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 7 publications
2
24
0
Order By: Relevance
“…For all cases, a 512x172 axisymmetric grid was employed to maintain consistency between the solutions. In each case, the grid was adapted to the shock layer to generate a quality heating profile and a cell Reynolds number of 1.0 was enforced at the surface 35 . Chemical or vibrational freezing in increments of 10% were independently considered up to 50%.…”
Section: Figure 7 Distribution Of Energy Modes For the Reservoir Conmentioning
confidence: 99%
“…For all cases, a 512x172 axisymmetric grid was employed to maintain consistency between the solutions. In each case, the grid was adapted to the shock layer to generate a quality heating profile and a cell Reynolds number of 1.0 was enforced at the surface 35 . Chemical or vibrational freezing in increments of 10% were independently considered up to 50%.…”
Section: Figure 7 Distribution Of Energy Modes For the Reservoir Conmentioning
confidence: 99%
“…Surface geometry definition and grid generation still remain the biggest bottlenecks in the CFD process. Papadopoulos et al (1999) stated that, "the factors that limit the use of CFD in the early design phase are how quickly the grids can be generated and how quickly 'sufficiently' accurate CFD simulations can be provided. For complex shapes, 10-100 CFD solutions with marginal fidelity but a very fast turn around time would allow CFD to be part of this stage."…”
Section: Methodsmentioning
confidence: 99%
“…Papadopoulos et al (1999) showed that, "a com putational mesh and a level of convergence which result in accurate surface-pressure and shear stress values do not guarantee accurate heat-transfer values." In addition, they found that both the level of convergence required for accurate predictions and the numerical algorithm used (including the flux-splitting method and the limiter used) could impact the results of a flow simulation at hypersonic speeds.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although these are good indicators, the true measure of grid quality is in the validation of the solution and depends on the specific physical problem (Papadopoulos et al, 1999). …”
Section: Grid Qualitymentioning
confidence: 99%